1996
DOI: 10.1177/002221949602900406
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computer-Assisted Versus Teacher-Directed Instruction on the Multiplication Performance of Elementary Students with Learning Disabilities

Abstract: The acquisition of multiplication facts by 4 elementary students with learning disabilities was compared under two instructional delivery formats-teacher directed and computer assisted. The two interventions were compared in terms of opportunities to respond and success rate. All students mastered more facts in the teacher-directed condition. In addition, teachers provided many more opportunities to respond and showed a higher success rate than did the software program. Implications of teacher-directed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Both students generalized CAI facts better than TAI facts. Wilson, Majsterek, and Simmons (1996) compared the effectiveness of computer-assisted instruction to teacherdirected instruction for teaching multiplication facts to four elementary students with learning disabilities. A single-subject, alternating treatment design was used to compare Math Blaster (Eckert & Davidson, 1987), a popular math software program, to teacher-directed practice flashcards.…”
Section: Computer-assisted Instruction Versus Teacher-directed Instrumentioning
confidence: 99%
“…Both students generalized CAI facts better than TAI facts. Wilson, Majsterek, and Simmons (1996) compared the effectiveness of computer-assisted instruction to teacherdirected instruction for teaching multiplication facts to four elementary students with learning disabilities. A single-subject, alternating treatment design was used to compare Math Blaster (Eckert & Davidson, 1987), a popular math software program, to teacher-directed practice flashcards.…”
Section: Computer-assisted Instruction Versus Teacher-directed Instrumentioning
confidence: 99%
“…Although the instructional format was matched, student performance was evaluated across two different modalities (i.e., computer responses and verbal responses), and this difference in response topographies may account for the mixed results. Wilson, Majsterek, and Simmons (1996) compared the effectiveness of the Math Blasters (Eckert & Davidson, 1987) computer program versus teacher instruction of multiplication facts in a sample of students with learning disabilities. Both the teacher's instruction and the Math Blasters program followed a model-guided, practice-independent practice format.…”
Section: Generalized Effects Of Computer-based Instructionmentioning
confidence: 99%
“…Given that the majority of teachers do not utilize computers to assess students' level of math performance (U.S. Department of Education, 2007), it is important to consider if generalization occurs when students are instructed on computers and then assessed using other formats, such as pencil and paper. As illustrated in the study by Wilson et al (1996), the dependent variable for all the students was their performance on paper-andpencil math probes; however, the students in the computer group did not practice with pencil and paper. This difference in the required response format for the practice responses versus the goal responses could have contributed to the lack of gains in performance for the computer group.…”
Section: Generalized Effects Of Computer-based Instructionmentioning
confidence: 99%
“…It is suggested that because of this consistent and efficient presentation of such antecedent-behaviorconsequence chains, CAI is a quality mode of instruction. In fact, research on CAI has suggested that it is effective for increasing mathematics performance among students without learning disabilities (e.g., Cosden & Abernathy, 1990;Kulik & Kulik, 1991;Okolo, 1992) and students with learning disabilities with mixed results (e.g., Christensen & Gerber, 1990;Torgesen, 1984;Wilson, Majsterek, & Simmons, 1996). However, one limitation of such procedures is cost.…”
Section: Computer-assisted Instructionmentioning
confidence: 99%